المحظورات النظامية لعملية التبرع بالأعضاء البشرية والعقوبات المترتبة عليها في النظام السعودي: دراسة مقارنة بالفقه الإسلامي - الفحام، عبدالله بن عبدالعزيز بن محمد (جامعة الأميرة نورة بنت عبد الرحمن, 2024)
تأتي هذه الدراسة للتعرف على محظورات التبرع بالأعضاء البشرية في النظام السعودي وموقف الفقه الإسلامي منها، وتتكون من مبحث تمهيد يتعلق بتعريف عنوان البحث ومن مبحثين، الأول محظورات التبرع بالأعضاء البشرية الخاصة بالأفراد والمنشآت، والثاني عن العقوبات المقررة في مخالفة عمليات زارعة الأعضاء البشرية. وقد سلكت المنهج الاستقرائي والمنهج المقارن، ومن أهم نتائج الدراسة استقراء (۱۲) محظور من المحظورات النظامية على الأفراد والمنشآت، وجميعها متوافقة مع أحكام الفقه الإسلامي، ومع نصوص النظام الأساسي للحكم، كما تم التوصل إلى وجوب الموازنة بين مصلحة المتبرع ومصلحة المتبرع له، وقد أجاز النظام السعودي نقل الأعضاء البشرية من الإنسان المتوفي بعد موافقة أقرب وارث له، وأجاز الوصية بالتبرع إذا كانت مكتوبة وموثقة ولم تعارض أحكام الشريعة الإسلامية وأحكام النظام حيث يجب على الأقارب تنفيذها. وأوصت الدراسة بالاقتراح على الجهات القضائية نشر الأحكام والقرارات المتعلقة بمخالفات التبرع بالأعضاء البشرية بشكل دوري، ومناسبة وضع حد أدنى للعقوبات المنصوص عليها للحد من التفاوت في الأحكام القضائية وهو ما يتوافق مع الرؤية المستقبلية للمملكة العربية السعودية في المنظومة العدلية، وزيادة التوعية بالمشكلات المتعلقة بالمخالفات وبيان خطورة ذلك عبر وسائل الإعلام المختلفة. This study aims to identify the prohibitions on human organ donation within the Saudi legal system and the stance of Islamic jurisprudence on these prohibitions. The study comprises an introductory section defining the research title and two main sections: the first discusses the prohibitions on organ donation for individuals and establishments, and the second examines the penalties prescribed for violations of organ transplantation procedures. The research employs both the inductive and comparative methods. Key findings of the study include identifying twelve regulatory prohibitions on individuals and establishments, all of which are consistent with Islamic jurisprudence and the provisions of the Basic Law of Governance. Additionally, the study emphasizes the necessity of balancing the interests of the donor and the recipient. The Saudi system permits the transfer of human organs from deceased persons with the consent of the nearest heir and allows for bequests of organ donation if written, documented, and not contrary to Islamic law and system regulations, in which case relatives must execute the will. The study recommends that judicial authorities periodically publish rulings and decisions related to violations of organ donation regulations, and suggests setting a minimum threshold for prescribed penalties to reduce disparities in judicial rulings, aligning with Saudi Arabia's future vision for the judicial system. Furthermore, it advocates for increased awareness of issues related to violations and their dangers through various media channels.
Keywords: الأعضاء البشرية -- مكافحة المخدرات -- قانون العقوبات -- النظام السعودي